Epistemological Beliefs And Their Effects On Reading Strategies, Metacognitive Strategies And Performance In An E-Learning Environment At Sultan Qaboos University - Sulaiyam Al Sakiti, Salim Rashid (2007)
Studies have shown that lecturers contribute significantly to the choice and use of reading and meta-cognition strategies to affect student performance and achievement.